Comparative evaluation for the sorption capacity of four carbonaceous sorbents to phenol. Issue 1 (1st October 2016) - Jin, Ding Feng; Xu, Yuan Yuan; Zhang, Ming; Jung, Yeong Sang; Ok, Yong Sik
Abstract: Sorption kinetics and isotherms of phenol by four carbonaceous sorbents (activated carbon (AC), mesoporous carbon (MPC), bamboo biochar (BBC) and oak wood biochar (OBC)) were compared in this study. MPC has the fastest sorption rate and initial sorption potential, which were indicated by sorption rate constants and initial sorption rate " h " in a pseudo-second-order kinetic model. The ordered and straight pore structure of MPC facilitated the accessibility of phenol. The AC showed the greatest sorption capacity towards phenol with maximum sorption of 123 mg/g as calculated by the Langmuir model. High surface area, complexity of pore structure, and the strong binding force of the π – π electron-donor-acceptor interaction between phenol molecules and AC were the main mechanisms. The BBC and OBC had much slower sorption and lower sorption capacity (33.04 and 29.86 mg/g, respectively), compared to MPC (73.00 mg/g) and AC, indicating an ineffective potential for phenol removal from water.